Association Between 10 Autoimmune Diseases and Risk of Pulmonary Tuberculosis: A Mendelian Randomization Study - Chen YE; Zhao GL; Liu FH (Journal of Multidisciplinary Healthcare)
Yue-E Chen,1,* Guo-Lian Zhao,2,* Fei-Hu Liu1 1GCP Institution Office, Xi’an Chest Hospital, Chest Hospital Affiliated to Northwest University, Xi’an, 710100, People’s Republic of China; 2Department of Clinical Laboratory, Xi’an Chest Hospital, Chest Hospital Affiliated to Northwest University, Xi’an, 710100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei-Hu Liu, GCP Institution Office, Xi’an Chest Hospital, Chest Hospital Affiliated to Northwest University, the Eastern Section of Aerospace Avenue, 2000 Duling West Road, Xi’an, 710100, Shaanxi, People’s Republic of China, Email feihuliu78@163.comBackground: Pulmonary tuberculosis (PTB) may have an autoimmune component. However, the cause of autoimmune diseases associated with PTB remains unclear. We performed a Mendelian randomization (MR) study to determine the causal genetic connections between liability to autoimmune diseases (AIDs) and PTB.Methods: After rigorous assessment, potential candidate SNPs for 10 AIDs and PTB were extracted from GWAS datasets. Three common MR approaches–inverse variance weighted (IVW), weighted median, and MR-Egger–were employed to assess causal relationships. To ensure the robustness of the findings, sensitivity analyses were performed to evaluate the stability of the results by estimating the heterogeneity and pleiotropy.Results: Our MR analysis indicated no discernible causal genetic connections between the seven AIDs, including rheumatoid arthritis (RA), asthma, Crohn’s disease (CD), systemic lupus erythematosus (SLE), psoriasis (PsO), multiple sclerosis (MS), ankylosing spondylitis (AS), and PTB (all P> 0.05). Interestingly, inflammatory bowel disease (IBD; OR, 0.967; 95% CI: 0.941– 0.994, P=0.015), celiac disease (CeD; OR, 0.944; 95% CI: 0.917– 0.972, P< 0.001), and primary sclerosing cholangitis (PSC; OR, 0.935; 95% CI: 0.877– 0.997, P=0.041) were significantly associated with a decreased risk of PTB. The sensitivity analyses confirmed the robustness of the results.Conclusion: Our MR observations collectively highlight that genetically predicted IBD, CeD, and PSC may be protective factors against PTB. However, there was no evidence of causal ramifications between the other seven AIDs (RA, asthma, CD, SLE, PsO, MS, and AS) and PTB, implying that unmeasured confounders or shared genetic structures may be the cause of the reported epidemiological associations.Keywords: pulmonary tuberculosis, PTB, autoimmune diseases, Mendelian randomization, MR, causal effects, risk factors